2022
DOI: 10.3390/ijerph19116866
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effects of Different Indoor Lighting Environments on Computer Work Fatigue

Abstract: The indoor lighting environment is a key factor affecting human health and safety. In particular, people have been forced to study or work more for long periods of time at home due to the COVID-19 pandemic. In this study, we investigate the influence of physical indoor environmental factors, correlated color temperature (CCT), and illumination on computer work fatigue. We conducted a within-subject experiment consisting of a 10 min-long task test under two different illumination settings (300 lx and 500 lx) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Objective experimental methods and physiological indicator measurements can quantify fatigue (Fang et al, 2022). Experiments involving work performance and differential attention tests have shown that both illuminance and color temperature are related to comfort and relaxation (Chen et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…Objective experimental methods and physiological indicator measurements can quantify fatigue (Fang et al, 2022). Experiments involving work performance and differential attention tests have shown that both illuminance and color temperature are related to comfort and relaxation (Chen et al, 2022a).…”
Section: Introductionmentioning
confidence: 99%